Implications of the rising cost of insulin and other antihyperglycaemic drugs in the management of diabetes mellitus in Nigeria - Otovwe Agofure (Advances in Medical, Pharmaceutical and Dental Research)
Abstract Diabetes mellitus stands as a paramount public health issue within Nigeria, deeply compounded by escalating costs of insulin and other hypoglycemic medications. The price surge, influenced by factors such as inflation and reliance on imports, significantly impedes access to vital drugs for numerous individuals managing diabetes in Nigeria. The resultant financial strain on patients’ insufficient healthcare infrastructure and subpar insurance coverage collectively precipitates deteriorated health outcomes and inflated healthcare expenditures. Non-adherence to prescribed medications due to prohibitive costs further amplifies complications and hospital admissions, thereby imposing significant pressure on both patients and the broader healthcare system. There is an imperative need for efficacious strategies encompassing drug price regulation, implementation of subsidies, encouragement of generic drug use, and enhancement of healthcare financing to address and alleviate these pervasive issues, ultimately fostering better diabetes management in Nigeria.   Received: 23 July 2024 Accepted: 14 November 2024 Published: 24 November 2024